Does robotics improve minimally invasive rectal surgery? Functional and oncological implications. Issue 2 (February 2016) - Guerra, Francesco; Pesi, Benedetta; Amore Bonapasta, Stefano; Perna, Federico; Di Marino, Michele; Annecchiarico, Mario; Coratti, Andrea
Abstract : Objective: Robot‐assisted surgery has been reported to be a safe and effective alternative to conventional laparoscopy for the treatment of rectal cancer in a minimally invasive manner. Nevertheless, substantial data concerning functional outcomes and long‐term oncological adequacy is still lacking. We aimed to assess the current role of robotics in rectal surgery focusing on patients' functional and oncological outcomes. Methods: A comprehensive review was conducted to search articles published in English up to 11 September 2015 concerning functional and/or oncological outcomes of patients who received robot‐assisted rectal surgery. All relevant papers were evaluated on functional implications such as postoperative sexual and urinary dysfunction and oncological outcomes. Results: Robotics showed a general trend towards lower rates of sexual and urinary postoperative dysfunction and earlier recovery compared with laparoscopy. The rates of 3‐year local recurrence, disease‐free survival and overall survival of robotic‐assisted rectal surgery compared favourably with those of laparoscopy. Conclusions: This study fails to provide solid evidence to draw definitive conclusions on whether robotic systems could be useful in ameliorating the outcomes of minimally invasive surgery for rectal cancer. However, the available data suggest potential advantages over conventional laparoscopy with reference to functional outcomes.